Coldening the Climate Through Elimination of Crematory Systems and Crematory Matter: A Review of Activities and Benefits for Peaceful Return of Migrants in the Global South - Pirot, Florent; Mezhennaya, Maria (European Journal of Applied Sciences, 2025)
It has been proven that crematory matter and crematory systems warm up the climate due to diffraction of gamma rays through the domineering shuriken atoms within. This has been confirmed through the destruction of crematory satellites with lasers, sodium-mash and a newer technology involving water-sodium-mashing of crematory satellites. The effects are local around the area of targeting but strong, with a minus 2°C observed. Water-sodium-mashing of crematory individuals has also worked significantly. This has been observed through experiments in three areas, with a reduction of up to 6 °C with 5 water-sodium-mashing systems working in the same location.